Season of the witch [compact disc, unabridged] : enchantment, terror, and deliverance in the City of love - Talbot, David, 1951- (Brilliance Audio, 2012)
In a kaleidoscopic narrative, bestselling author David Talbot recounts the gripping story of San Francisco in the turbulent years between 1967 and 1982--and of the extraordinary men and women who led to the city's ultimate rebirth and triumph. Season of the Witch is the first book to fully capture the dark magic of San Francisco in this breathtaking period, when the city radically changed itself--and then revolutionized the world. The cool gray city of love was the epicenter of the 1960s cultural revolution. But by the early 1970s, San Francisco's ecstatic experiment came crashing down from its starry heights. The city was rocked by savage murder sprees, mysterious terror campaigns, political assassinations, street riots, and finally a terrifying sexual epidemic. No other city endured so many calamities in such a short time span.